Pengaruh Penerapan Multimedia ICT Pembelajaran IPA Terhadap Pemahaman Konsep Siswa : The Effect of Implementing ICT-Based Multimedia in Science Learning on Students’ Conceptual Understanding - Stiosarint, Yulantika; Ntobuo, Nova Elysia; Supartin, Supartin; Amali, Lanto Mohamad Kamil; Uloli, Ritin; Odja, Abdul Haris (Institut Agama Islam Daruttaqwa Gresik, 2025)
. Understanding science concepts among junior high school students is a crucial aspect because science requires the ability to reason, make connections, and apply scientific concepts in everyday life. However, low levels of conceptual understanding are still frequently found, partly due to the dominance of conventional teaching methods and the limited use of technology. Information and Communication Technology (ICT)–based multimedia is considered to have the potential to improve the quality of learning through visual, audio, and interactive presentations of material. This study aims to analyze the effect of implementing ICT-based multimedia in science learning on students’ conceptual understanding. The study employed a quasi-experimental method with a one-group pretest–posttest design. The research subjects were ninth-grade students of SMP Negeri 3 Gorontalo, consisting of two classes (Class IX C = 21 students; Class IX D = 22 students), selected using saturated sampling (N = 43). The research instrument was an essay test of conceptual understanding based on the indicators of interpreting, exemplifying, classifying, summarizing, inferring, comparing, and explaining. Data were analyzed using the Kolmogorov–Smirnov normality test, Levene’s homogeneity test, and hypothesis testing with a One-Sample t-Test at a significance level of 0.05. The results showed that the mean scores increased from pretest to posttest in both classes (57.54 to 88.10; 55.78 to 86.74). The One-Sample t-Test indicated that the posttest scores were significantly higher than the minimum mastery criterion (KKM) of 75 (Sig. = 0.000). These findings imply that ICT-based multimedia is effective as a science learning strategy to strengthen students’ conceptual understanding at the junior high school level.